2017
DOI: 10.11628/ksppe.2017.20.1.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Urban Agriculture Experience Program on the Mental Health of the Elderly

Abstract: This study investegated the positive effect of the urban agriculture experience program on the mental health of the elderly by measuring the mental health indices of stress and depression. The research subjects included an experiment group of seniors over 65 years old who participated in the program for over six months and a control group of seniors, whom resided in the same city. Stress and depression were surveyed as mental health indices, and the physiological disparity was measured to clarify the disparity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…On the other hand, the stress of index of the two control groups increased although the increase was not statistically significant. These results were similar to the results of Kang and Back (2017) that the stress index of elderly people obtained by measuring pulse waves decreased after participating in an urban agricultural experience program. In addition, another study that analyzed the level of cortisol, a stress hormone, in the body to examine changes in physiological stress after performing a horticultural therapy program (Han et al, 2018) also reported a decrease in the physiological stress after treatment, which was similar to the results of this study.…”
Section: Effects Of the Horticultural Activity Program (Hap) On Changsupporting
confidence: 88%
“…On the other hand, the stress of index of the two control groups increased although the increase was not statistically significant. These results were similar to the results of Kang and Back (2017) that the stress index of elderly people obtained by measuring pulse waves decreased after participating in an urban agricultural experience program. In addition, another study that analyzed the level of cortisol, a stress hormone, in the body to examine changes in physiological stress after performing a horticultural therapy program (Han et al, 2018) also reported a decrease in the physiological stress after treatment, which was similar to the results of this study.…”
Section: Effects Of the Horticultural Activity Program (Hap) On Changsupporting
confidence: 88%
“…Agro-healing activities that utilize plants and nature as a medium were reported to be effective in improving children and adolescents' self-efficacy, psychological wellbeing, self-esteem and sociality and for increasing psychological and emotional relaxation such as reducing aggression, stress and depression (Kang et al, 2012;Keum, 2014;Park and Kim, 2010;Shin, 2010;Soga et al, 2017;Yun and Yoo, 2011). They were also reported to have positive effects on the mental health of adults such as reducing their depression and stress and to be helpful in maintaining their physical health by reducing blood pressure (Jang, Gim, et al, 2019;Jang, Yoo, et al, 2019), and to have other various effects such as improving the mental health of the elderly by reducing a sense of loneliness, depression and stress, improving cognitive functions, the performance of daily life activities and life satisfaction (Kang and Back, 2017;Kim and Yoo, 2010;Lee and Sim, 2004;Oh and Yoo, 2010;Yoo and Jeong, 2010). Seol et al (2019) proved that activities of producing and selling horticultural products were effective for the vocational rehabilitation of those with mental disorders, and You and Shin (2019) reported that forest experiences can promote the visual perception of children with mental disabilities.…”
Section: Introductionmentioning
confidence: 99%